The Bioactive Constituents of Piper aduncum L. as Estrogen Receptor-α Inhibitors: in silico studies - Shafa, Nafis; Lathifah, Salma Sri; Alifa, Zahra; Syahid, Muhammad; Ismail, Dzava Prawinsyah Fairus; Mahardika, Bintang Satrio; Novitasari, Dhania (Indonesian Journal of Biological Pharmacy, 2025)
Wild betel (Piper aduncum L.) is a traditional medicinal plant with reported anticancer potential, particularly against breast cancer. Breast cancer remains a leading cause of cancer-related mortality worldwide, largely driven by estrogen receptor alpha (ERα)–mediated tumor growth. This study aimed to evaluate the potential of bioactive compounds from P. aduncum as ERα inhibitors using an in silico approach. Twenty compounds identified from P. aduncum were assessed for drug-likeness and ADMETox properties, followed by pharmacophore modeling and molecular docking against ERα. Phlorizin, linalool, and phloretin exhibited the highest pharmacophore fit scores, with the optimal model demonstrating strong predictive performance (AUC = 0.95). Among these compounds, phlorizin showed the strongest binding affinity for ERα (−10.38 kcal/mol), with a predicted inhibition constant of 24.77 µM, forming key interactions with GLU353, ALA350, and LEU525, comparable to those of the reference ligand 4-hydroxytamoxifen. Overall, these findings indicate that P. aduncum–derived compounds, particularly phlorizin, phloretin, and linalool, are promising ERα inhibitor candidates and merit further experimental validation for breast cancer therapy.